Finiteness Properties of Minimax and a-Minimax Generalized Local Cohomology Modules - Kianezhad, A.; Taherizadeh, A. J. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
Let R be a commutative Noetherian ring with nonzero identity, let a be an ideal of R, and let M and N be two (finitely generated) R-modules. We prove that H_a ^i( M,N ) is a minimax a-cofinite R-module for all i